Socio-Cultural Meaning of the Uang Panaik Tradition for the Bugis Community of Jeruju Besar Village - Syauqiyah, Sabilah; Ramadhan, Iwan (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to describe the socio-cultural meaning of the uang panaik tradition among the Bugis community in Desa Jeruju Besar, Kecamatan Sungai Kakap, West Kalimantan. Uang panaik is a sum of money given by the groom’s family to the bride’s family prior to the wedding. From the perspective of the Bugis people, uang panaik is not merely about material wealth, but also represents responsibility and honor (siri’) toward the bride and her family. This study employs a descriptive qualitative method, using observation, interviews, and documentation as data collection techniques involving customary leaders, young couples, and Bugis youth in Desa Jeruju Besar. The results indicate that the Bugis community in Desa Jeruju Besar still upholds the uang panaik tradition as part of their cultural identity. Values such as family solidarity and mutual respect are maintained through deliberation in determining the amount of uang panaik. However, some community members have begun adjusting the amount to avoid creating an economic burden for the groom’s side. This demonstrates that the uang panaik tradition not only persists as a cultural symbol but also continues to adapt to the evolving social and economic context of the community.